Weld Geometry Investigation on Dissimilar Boron Steel Laser Welded for TWB Application - M. N. M., Salleh; M., Ishak; M. H., Aiman; M. M., Quazi; A. M., Hanafi (Universiti Malaysia Pahang, 2019)
The pulse wave (PW) mode is an excellent replacement for continuous wave (CW) mode f laser welding in the tailor-welded blank (TWB) application for the automotive ndustry. Due to its ability to produce higher peak power in low power laser pulse mode, he weld penetration and high weld quality can be achieved similarly to the utilization of very high power laser of CW mode. This present work was carried out to investigate the ffect of pulse laser welding parameters of a dissimilar thickness of boron steel for the TWB application. Low power fibre laser with 200 W average power was chosen in this xperimental work. Response surface method (RSM) was used for the design of xperiment (DOE) by applying Box-behnken design (BBD) since there were three rocess factors involved. The process factors are peak power (PP), welding speed (WS) nd focal position (FP) and tensile strength is the response for the weld joint. The metallurgical analysis was conducted at the cross section of sample possessing highest nd lowest tensile strength. Boron steel was successfully welded by using low power fibre aser with PW mode in butt joint configuration. It was found that the highest tensile trength possessed fracture located at the base metal, which is convincing the strength of he joint. For microstructure, finer grain produced at the centre of the fusion zone (FZ) ompared to the FZ near the transition line which produced coarser and medium grain. Finer grain size in FZ contributes to the higher microhardness value and tensile strength f the joint compared to the BM region.